Contribuição ao estudo do contato elástico entre um cilindro e um plano, com atrito seco - Saramago, Sezimária de Fátima Pereira (1990)
A contri buti on to the study of the slip less contact between two elastic bodies, using the Coulomb’s dry friction model, is presented. The mathematical model for the problem of a cylinder in contact with a plane is obtained by the superposi tion of the displacement by the normal and tangential stress acting in the contact area. The pressure distribution and boundary of the contact area are determined by the minimization of the elastic energy function, by using the Augmented Lagrange Multiplier Optimization method, adopting the coefficients of a third degree polynomial and the limits of the contact area as decision variables.